An Australian Example of Translating Psychological Research into Practice and Policy: Where We are and Where We Need to Go - Werner-Seidler, Aliza; Perry, Yael; Christensen, Helen (Frontiers in Psychology, 2016)
Research findings from psychological science have identified interventions that will benefit human health. However, these findings are not often incorporated into practice-based settings or used to inform policy, in part, due to methodological and contextual limitations. A strategic approach is required if we are to find a way to facilitate the translation of these findings into areas that will offer genuine impact on health. There is an overwhelming focus on conducting more clinical trials, without consideration of how to ensure that findings from such trials make it to the patients or populations for whom they were intended. The aim of this paper is to outline how the Black Dog Institute, an Australian medical research institute, has created a framework designed to facilitate the translation of research findings into practice-based community settings, and how these findings can be used to inform policy. We propose that the core strategies adopted at the Black Dog Institute to prioritise and implement a translational program will be useful to institutes and organisations worldwide to augment the impact of their work. We provide several examples of how our research has been implemented in practice-based settings at a community-level, and how we have used research in psychology as a platform to inform policy change.